HUKUM PERJANJIAN DAN AKAD TRANSAKSI SYARIAH DI INDONESIA (Tujuh Indikator Keberhasilan Dan Kegagalan Dalam Kacamata Islam) - KOMARI, KOMARI (EKSYAR: Jurnal Ekonomi Syari'ah & Bisnis Islam, 2017)
A contract or agreement must meet the requirements of the validity of the agreement, that is an agreement, proficiency, certain things and a lawful cause, as defined in article 1320 of the Civil Code. With the fulfillment of four conditions of validity of the agreement, then a treaty becomes lawful and legally binding for the parties that make it. The Definition of the Law The Syariah Agreement is a deliberately written engagement, so it can be used as evidence for the parties concerned. The contemporary forms of ijtihad of the ulama have now been formed by the National Sharia Council (DSN) which is part of the Indonesian Ulema Council (MUI). This is what enables the Law of the Shariah Covenant to keep up with the times. By using ijtihad result, contemporary scholars who are well versed in the technicalities of business transactions prevailing in today's modern times, but the Law of the Syariah Agreement can still be executed in accordance with the original rules.